ANALISIS KEPUTUSAN PETANI MELAKUKAN PEMUPUKAN PADA TANAMAN KOPI DI DESA PULAU BERINGIN KECAMATAN PULAU BERINGIN KABUPATEN OGAN KOMERING ULU SELATAN (JASEP, 2019)
This study aims to determine what factors influence the decision of farmers to fertilize the coffee plant in the village of Banyan Island. This research was conducted in Beringin Island Village. The research data was collected using survey method which used 50 farmers sample. The sampling method used in this study is randomized layered unbalanced (disproportionate stratified random sampling). The method of processing datan using binary logistic regression analysis. The result of the research can be concluded that what factors influence the decision of the farmer to fertilize the coffee plant in Beringin Village, South Ogan Komering Ulu Regency that significantly influence the price of urea fertilizer, the price of ponska fertilizer, the price of pearl fertilizer, the income, the land area , cost, frequency of counseling, education and access in obtaining fertilizer. While the price of KCL fertilizer did not significantly affect the farmer's decision to fertilize the coffee plant in Beringin Village, South Ogan Komering Ulu Regency.